2004
DOI: 10.1038/nature02877
|View full text |Cite
|
Sign up to set email alerts
|

Spermatid differentiation requires the assembly of a cell polarity complex downstream of junctional adhesion molecule-C

Abstract: During spermatogenesis in the mammalian testis, stem cells (spermatogonia) differentiate into spermatocytes, which subsequently undergo two consecutive meiotic divisions to give rise to haploid spermatids. These cells are initially round but progressively elongate, condense their nuclei, acquire flagellar and acrosomal structures, and shed a significant amount of their cytoplasm to form spermatozoa (the sperm cells) in a developmental cascade termed spermiogenesis. Defects in these processes will lead to a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
284
2
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(310 citation statements)
references
References 29 publications
23
284
2
1
Order By: Relevance
“…Transmembrane proteins of the immunoglobulin family have been known to confer adhesion between Sertoli and germ cells via heterotypical interactions. For example, nectin-2 and nectin-3 form heterotypical complex at the Sertoli-spermatid interface [35], and likewise JAM-B on the Sertoli cell side interact with JAM-C on spermatids in mouse testes [17]. In this study, we were not able to immunoprecipitate CAR with JAM-C using protein lysate from rat testes or Sertoli cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Transmembrane proteins of the immunoglobulin family have been known to confer adhesion between Sertoli and germ cells via heterotypical interactions. For example, nectin-2 and nectin-3 form heterotypical complex at the Sertoli-spermatid interface [35], and likewise JAM-B on the Sertoli cell side interact with JAM-C on spermatids in mouse testes [17]. In this study, we were not able to immunoprecipitate CAR with JAM-C using protein lysate from rat testes or Sertoli cells.…”
Section: Discussionmentioning
confidence: 62%
“…More importantly, these proteins work in concert to facilitate the movement of germ cells [15]. To date, knockout studies of nectin-2 and JAM-C have yielded mice that were defective in spermatogenesis [16,17], illustrating the essential roles of these adhesion molecules in spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The insights gained by using an in vitro cell system that expresses only one JAM isoform can guide studies of liver development in vivo, where the lack of liver phenotypes in any of the three JAM knockout mice points to overlapping functions for the protein (8,21,56). Future studies using the KD cells to express different JAM isoforms and mutant constructs should also provide further understanding of this protein's role in the complex polarity of hepatic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although epithelial functions have been disrupted by JAM-A knockdown (KD) in cell culture models of simple epithelia and recently in cultured hepatic cells (35,54), gene knockout studies of individual JAMs in mice have shown no major defects in development or function of epithelia, most likely a consequence of gene redundancy (8,21,56). Nonetheless, results from the in vitro studies suggest that JAM plays an essential and early role in TJ formation (17,26,38), since it was found at primordial cell-cell contact sites in a bronchial epithelial cell line (31).…”
mentioning
confidence: 99%
“…Leçons des souris JAM-C knock-out L'étude des souris Jam-C -/-a révélé un phénotype de stérilité des mâles lié à un défaut de polarité des spermatogonies dû à l'absence de JAM-C dans des structures adhésives présentes entre spermatozoïdes et cellules de Sertoli et appelées spécialisations ectoplasmiques [9]. Par ailleurs, la perte de l'activité adhésive de JAM-C exprimée par l'endothélium résulte en une susceptibilité accrue des souris Jam-C -/-aux infections opportunistes et en une perte de la régulation de l'homéostasie des neutrophiles sanguins [10].…”
unclassified